If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(d + -4) + -8 = 5(5d + 1) + -3 Reorder the terms: 3(-4 + d) + -8 = 5(5d + 1) + -3 (-4 * 3 + d * 3) + -8 = 5(5d + 1) + -3 (-12 + 3d) + -8 = 5(5d + 1) + -3 Reorder the terms: -12 + -8 + 3d = 5(5d + 1) + -3 Combine like terms: -12 + -8 = -20 -20 + 3d = 5(5d + 1) + -3 Reorder the terms: -20 + 3d = 5(1 + 5d) + -3 -20 + 3d = (1 * 5 + 5d * 5) + -3 -20 + 3d = (5 + 25d) + -3 Reorder the terms: -20 + 3d = 5 + -3 + 25d Combine like terms: 5 + -3 = 2 -20 + 3d = 2 + 25d Solving -20 + 3d = 2 + 25d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-25d' to each side of the equation. -20 + 3d + -25d = 2 + 25d + -25d Combine like terms: 3d + -25d = -22d -20 + -22d = 2 + 25d + -25d Combine like terms: 25d + -25d = 0 -20 + -22d = 2 + 0 -20 + -22d = 2 Add '20' to each side of the equation. -20 + 20 + -22d = 2 + 20 Combine like terms: -20 + 20 = 0 0 + -22d = 2 + 20 -22d = 2 + 20 Combine like terms: 2 + 20 = 22 -22d = 22 Divide each side by '-22'. d = -1 Simplifying d = -1
| 24x^2+18x+3=0 | | 36=9(v-3) | | sin(5x)cos(10x)+cos(5x)sin(10x)= | | 2y-1=5-8(y+5) | | -11=5u-1 | | sin(4x)cos(7x)+cos(7x)sin(4x)= | | -47=9-7v | | x+12x+50=180 | | 2(x-3)+5=1+3x | | 89=3x+5x-7 | | -2.4x+9=8 | | f(x)=2x^8-3x | | 3(x+4x)+3x= | | 1.2x+4=9 | | 8w^2-4w-4=0 | | (3x+7)(6x+3)=0 | | 10x+15=68-8x | | .25n(6n-3)=4n+1 | | A+3a-5=-78 | | 2p+(-3)(1-p)=(-2)p+1(1-p) | | (D/7)-1=8 | | 6b^2=48 | | 5g-7.8=62.7 | | 2p^2-6p-9=0 | | 2x+7x+9=0 | | 5z^2-9z-7=0 | | 24x^2+100x+100=0 | | 7x-4=57 | | y=0.05x^2-x+480 | | -6j+18=3j-3 | | 8m^2-6=0 | | 17+x=130 |